2021
DOI: 10.17582/journal.aavs/2022/10.3.676.684
|View full text |Cite
|
Sign up to set email alerts
|

Leverage of Chromium Methionine Supplementation in Laying Japanese Quail’s Diets on Performance, Quality, and Blood Traits Challenged by Heat Stress

Abstract: T ypical of developing countries that are very vulnerable to climate change and face multiple economic and environmental sustainability challenges, Egypt stands out as a good illustration of this. Egypt's existing arid climate will be exacerbated by climate change, with relatively high temperatures and poorer rainfall in major agricultural areas. All ecological conditions affect animal welfare, including temperature, humidity, presence of toxic contaminants, and litter quality (Utnik-Banaś et al., 2014). In the Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Minerals play an important role in nutritional and physiological efficiency (Khalifah et al, 2022) Zn is an essential element in the alimentation of humans and an animal, besides being required in the genetic structure of every cell and are a critical requirement in all biological reproduction traits, also, in all DNA, RNA syntheses and its needed for every step of the cell cycle (Chrastinova et al, 2015). Attia et al (2016) reported that supplementing rabbits with Zn significantly increased live weight gains and affected feed utilization during the metabolism of carbohydrates, lipids, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Minerals play an important role in nutritional and physiological efficiency (Khalifah et al, 2022) Zn is an essential element in the alimentation of humans and an animal, besides being required in the genetic structure of every cell and are a critical requirement in all biological reproduction traits, also, in all DNA, RNA syntheses and its needed for every step of the cell cycle (Chrastinova et al, 2015). Attia et al (2016) reported that supplementing rabbits with Zn significantly increased live weight gains and affected feed utilization during the metabolism of carbohydrates, lipids, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…After banning the antibiotics as growth promoters, the world is looking forward to the natural alternatives of antibiotics because of the increasing demand for antibiotic-free and organic poultry products. Amino acids, vitamins, minerals, and enzymes are already used as dietary supplements to maintain the normal physiological status, support the immune response and enhance poultry productivity under thermo-neutral and heat stress conditions (Ebeid 2009(Ebeid , 2012Saleh et al 2019Saleh et al , 2020Abdel-Moneim et al 2021;Khalifah et al 2022). Probiotics, prebiotics, synbiotics, and organic acids might be promising alternatives to antibiotic growth promoters in poultry production because of their capability to maintain balanced microbial populations in the gastrointestinal tract (GIT), establish intestinal integrity, and support the immune response in poultry (Wei et al 2022;Ebeid and Al-Homidan 2022).…”
mentioning
confidence: 99%